2015
DOI: 10.1038/srep17455
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen cytotoxicity is ameliorated in a human liver organotypic co-culture model

Abstract: Organotypic liver culture models for hepatotoxicity studies that mimic in vivo hepatic functionality could help facilitate improved strategies for early safety risk assessment during drug development. Interspecies differences in drug sensitivity and mechanistic profiles, low predictive capacity, and limitations of conventional monocultures of human hepatocytes, with high attrition rates remain major challenges. Herein, we show stable, cell-type specific phenotype/cellular polarity with differentiated functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 59 publications
4
38
0
Order By: Relevance
“…Conversely, we also investigated whether hPSC‐ECs could, in turn, impact the metabolic function of hPSC‐HEPs in a coculture setting. It has been reported that endothelial cells could improve hepatic function [] and provide some levels of hepatoprotection from acetaminophen toxicity []. In our study, cocultured hPSC‐HEPs had comparable albumin levels with monocultured hPSC‐HEPs (supplemental online Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Conversely, we also investigated whether hPSC‐ECs could, in turn, impact the metabolic function of hPSC‐HEPs in a coculture setting. It has been reported that endothelial cells could improve hepatic function [] and provide some levels of hepatoprotection from acetaminophen toxicity []. In our study, cocultured hPSC‐HEPs had comparable albumin levels with monocultured hPSC‐HEPs (supplemental online Fig.…”
Section: Resultssupporting
confidence: 64%
“…Multicellular coculture models [, , ] are gaining momentum for various applications. A recent study described the use of human umbilical vein endothelial cells to stabilize hepatoblastoma C3A cells and modulate drug‐induced hepatotoxicity []. Endothelial cells from hPSCs were used to vascularize liver constructs [].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the levels of CYP2C9 and CYP3A4 enzyme activity in hASC-HLCs-Chir99021 were relatively higher than that in hASC-HLCs-activin A. These data imply that hASC-HLCs in this study more closely resemble human hepatocytes for pre-clinical assessment of new candidate compounds in drug development33. Of course many efforts are still needed for promoting hASC-HLCs further maturation under the hepatic microenvironment, until they have equal metabolic abilities compared with human adult hepatocytes.…”
Section: Discussionmentioning
confidence: 51%
“…It is not clear what interactions caused decreased viability of HepaRG cells in the presence of HUVECs relative to LSECs. In addition, these interactions seem to be unique as the results obtained using the HepG2‐derived C3A cell line, in combination with HUVEC is shown to promote the survival of hepatocytes (Nelson et al, ). Those co‐cultures showed improvements in albumin synthesis by day 3 and less toxicity towards APAP.…”
Section: Discussionmentioning
confidence: 99%